A GIANT AMONG GIANTS: A NEW LAND TORTOISE FROM THE PLEISTOCENE OF THE ARGENTINE PAMPAS (Rivista italiana di Paleontologia e Stratigrafia, 2025)
Gigantism in terrestrial tortoises occurred frequently and convergently in different lineages of Testudinidae. Despite the fact that giant forms were geographically and stratigraphically widespread in South America, Pleistocene members are still very poorly known, most of them represented by fragmentary and unassociated materials. The aim of the present contribution is to describe Chelonoidis pucara n. sp., a new species coming from Upper Pleistocene beds of northern Buenos Aires province, Argentina. The new species is known by the anterior half of a plastron having a unique combination of apomorphic and plesiomorphic features. It is very large-sized (estimated carapace length about 1.7-1.8 meters), rendering it as the largest testudinid from South America, and placing it among the “supergigantic” tortoise phenotype. Like other supergigantic tortoises (which were up to now exclusively known in the Old World), the new species shows enlarged epiplastral projections, probably related to competition with other males. The ecological role of these “supergigantic” tortoises is also briefly discussed.